Risk of Nutritional Status and Blood Sugar on Type 2 Diabetes Mellitus with Pulmonary Tuberculosis in Sawahan Subdistrict, Surabaya, Indonesia - Ana Mala Fitri1 , Muhammad Atoillah Isfandiari1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The diabetics have risk of pulmonary tuberculosis It caused by lacking of immune system and malnutrition, eventhough the diabetics’ nutritional status commonly is normal or overweight. This research aimed to analyze risk of nutritional status and blood sugar to patients of diabetes mellitus with pulmonary tuberculosis. The study was observational analytic with case control design. There were 20 samples in each case and control located in Sawahan Sub-district, Surabaya. The data collection used questionnaire and medical record of participants from the community health care. The data was analysed using Pearson test correlation and odd ratio. The result showed no correlation between body mass index and blood sugar of both random (p=0.138) and fasting (p=0.166). The oberweight diabetics are much more likely to get pulmonary tuberculosis 1.3 times compared to normal diabetics (95% CI= 0.313<OR<5.393), while the odd ratio of pulmonary tuberculosis in underweight diabetics is estimated to be 1.2 times compared to diabetics who are normal (95% CI= 0,121<OR<11,865). The diabetics who have random blood sugar level of ?200 mg/dL are 0.46 times to have pulmonary tuberculosis compared to blood sugar level of <200 mg/dL (95% CI=0.111<OR<1.94). The diabetics who have fasting blood sugar level of ?126 mg/dL showed effect 2.43 times to be likely get pulmonary tuberculosis either they have <126 mg/dL 95% CI= 0.51<OR<11.51). There was no relationship between blood sugar level, nutritional status, and pulmonary tuberculosis on patients with type 2 diabetes mellitus.